Multi-Subject Image Retrieval by Fusing Object and Scene-Level Feature Embeddings - Ban, Chung-Gi; Hwang, Youngbae; Park, Dayoung; Lee, Ryong; Jang, Rae-Young; Choi, Myung-Seok (Applied sciences, 2022)
Most existing image retrieval methods separately retrieve single images, such as a scene, content, or object, from a single database. However, for general purposes, target databases for image retrieval can include multiple subjects because it is not easy to predict which subject is entered. In this paper, we propose that image retrieval can be performed in practical applications by combining multiple databases. To deal with multi-subject image retrieval (MSIR), image embedding is generated through the fusion of scene- and object-level features, which are based on Detection Transformer (DETR) and a random patch generator with a deep-learning network, respectively. To utilize these feature vectors for image retrieval, two bags-of-visual-words (BoVWs) were used as feature embeddings because they are simply integrated with preservation of the characteristics of both features. A fusion strategy between the two BoVWs was proposed in three stages. Experiments were conducted to compare the proposed method with previous methods on conventional single-subject datasets and multi-subject datasets. The results validated that the proposed fused feature embeddings are effective for MSIR.